Sensibilidade do custo da energia elétrica fotovoltaica no Brasil utilizando o método de Monte Carlo - Schram, Igor Bertolino (2019)
Faced with the demand for solar energy from alternative sources, in addition to being clean and renewable, photovoltaic solar energy is an increasingly attractive option. Thus, an investment feasibility analysis is required in a solar photovoltaic installation. In this work, an analysis of the cost variability of the installation of the photovoltaic system in Brazil (R$/kWp) by the Monte Carlo method is carried out and compared to the variation in countries where the technology is already established and developed in the world, such as China, United States and Germany. Also by the Monte Carlo method, it is evaluated the levelized cost of energy (R$/kWh) in the different regions of the country and is considered an electric energy tariff for its viability. In addition, a combination of photovoltaic systems in Brazil is analyzed and the viability of different powers installed at different levels of solar energy in the extension of the national territory is analyzed. All analyzes are based on official documents and scientific papers. The cost of photovoltaic systems in Brazil has an average value of about 2,100 $/kWp, lower than that of the United States and decreases exponentially as the power of the system increases. The viability occurs in different ways in each region of Brazil and at different levels of solar radiation. The Northeast region appears as the most feasible to invest in photovoltaic systems among all regions. It was found that the variability depends mainly on the level of solar radiation, the power of the photovoltaic system and the current electric energy tariff charged by the local utility.